2020
DOI: 10.1039/d0ra05797e
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of scandium and neodymium from blast furnace slag using acid baking–water leaching

Abstract: An environmentally sustainable pyro-hydrometallurgical process, called acid baking–water leaching, helps enable the extraction of scandium and neodymium from ironmaking slag to establish the circular economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Moreover, water leaching at 90 • C achieved a faster kinetic reaction than lower temperatures [22]. Kim and Azimi (2020) studied the extraction of slag rich in rare-earth elements using acid baking, and the authors also stated that the water leaching achieved a plateau after 120 min in all cases, and the kinetic rate was faster at 90 • C than lower temperatures [23]. Zou et al (2021) demonstrated that lanthanum and cerium extraction also achieved a plateau after 120 min in leaching after the baking process from rare-earth polishing powder wastes [24].…”
Section: Dry Digestion and Acid Baking Experimentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, water leaching at 90 • C achieved a faster kinetic reaction than lower temperatures [22]. Kim and Azimi (2020) studied the extraction of slag rich in rare-earth elements using acid baking, and the authors also stated that the water leaching achieved a plateau after 120 min in all cases, and the kinetic rate was faster at 90 • C than lower temperatures [23]. Zou et al (2021) demonstrated that lanthanum and cerium extraction also achieved a plateau after 120 min in leaching after the baking process from rare-earth polishing powder wastes [24].…”
Section: Dry Digestion and Acid Baking Experimentsmentioning
confidence: 97%
“…Concentrated sulfuric acid was mixed with the material and heated at 200-400 • C. Then, the resulting material was leached with water for the extraction of rare-earth elements, where equilibrium was achieved within 2 h at 90 • C [22]. Kim and Azimi (2020) studied the extraction of slag rich in rare-earth elements using acid baking, and the authors also stated that water leaching achieved a plateau after 120 min in all cases, and the kinetic rate was faster at 90 • C than lower temperatures [23]. Zou et al (2021) demonstrated that lanthanum and cerium extraction also achieved a plateau after 120 min from rare-earth polishing powder wastes after the baking process [24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, neodymium and dysprosium are key components of permanent magnets, such as NdFeB magnets. The demand for the separation and recovery of dysprosium and neodymium from used permanent magnets and scraps generated during manufacturing is increasing [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the material resulted was leached with water for extraction of rare earth elements, where achieved the equilibrium within 2h at 90˚C [164]. Kim & Azimi (2020) studied the extraction of slag rich in rare earth elements by acid baking, and the authors also stated that the water leaching achieved the plateau after 120min in all cases, and the kinetic rate is faster at 90˚C than lower temperatures [364]. Zou et al (2021) demonstrated that lanthanum and cerium extraction also achieved the plateau after 120min from rare earth polishing powder wastes after the baking process [365].…”
Section: Introductionmentioning
confidence: 99%
“…The authors state that the water leaching achieved equilibrium within 2h of the process. Moreover, water leaching at 90˚C achieves a faster kinetic reaction than at lower temperatures[164] Kim & Azimi (2020). studied the extraction of slag rich in rare earth elements by acid baking, and the authors also stated that the water leaching achieved the plateau after 120min in all cases, and the kinetic rate is faster at 90˚C than lower temperatures[364] Zou et al (2021).…”
mentioning
confidence: 99%